FEM Analysis of PMH Stepper Motor Using PDETOOL Simulations of Matlab for Different Topoligies - E.V.C Sekhara Rao; P.V.N. Prasad (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
This paper discuss about simulation of permanent magnet hybrid stepper motor (PMH) magnetic circuit using finite element model using PDE toolbox of Matlab. It concludes mmf distribution during excitation due to permanent magnet and excitation coil for eight topologies. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.856